2012
DOI: 10.1021/es302042t
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Structure in the Drinking Water Microbiome Is Governed by Filtration Processes

Abstract: The bacterial community structure of a drinking water microbiome was characterized over three seasons using 16S rRNA gene based pyrosequencing of samples obtained from source water (a mix of a groundwater and a surface water), different points in a drinking water plant operated to treat this source water, and in the associated drinking water distribution system. Even though the source water was shown to seed the drinking water microbiome, treatment process operations limit the source water's influence on the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
318
7
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(371 citation statements)
references
References 38 publications
45
318
7
1
Order By: Relevance
“…At the genus taxonomic level the presence of large proportions of phylotypes belonging to the genera Acidovorax, Curvibacter and Gemmata, and the family Commamonadaceae in our study was similar to other findings in fresh water samples from around the world (Pinto et al 2012;Lautenschlager et al 2013;Navarro-noya et al 2013). …”
Section: Moreira Et Al 2011)supporting
confidence: 91%
“…At the genus taxonomic level the presence of large proportions of phylotypes belonging to the genera Acidovorax, Curvibacter and Gemmata, and the family Commamonadaceae in our study was similar to other findings in fresh water samples from around the world (Pinto et al 2012;Lautenschlager et al 2013;Navarro-noya et al 2013). …”
Section: Moreira Et Al 2011)supporting
confidence: 91%
“…Eichler et al (2006) found that no major changes of bacterial community structures occurred after flocculation and sand filtration. In contrast, Pinto et al (2012) found that filtration by dual media rapid sand filters could shape the bacterial community in waters. Based on the significant difference between bacterial communities in raw water and on BAC, Soonglerdsongpha et al (2011) suggested that bacterial community structure changed along the BAC filtration process.…”
Section: Bacterial Community Structuresmentioning
confidence: 89%
“…Pinto et al (2012) found that filtration by dual media rapid sand filters in a drinking water plant played a primary role in shaping the bacterial community in DWDS. The main aim of the current study was to assess bacterial community change through drinking water treatment processes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used high-throughput sequencing technologies to investigate bacterial community diversity in water distribution systems locations or components (Kwon, 2011;Pinto et al, 2012;Douterelo et al, 2013;Navarro-Noya et al, 2013). In a recent study, we highlight the importance for such investigations in First Nations communities in Canada (Fernando et al, 2016).…”
Section: Introductionmentioning
confidence: 95%